PENGARUH PRODUCT QUALITY AND PRICE PERCEPTION TERHADAP CUSTOMER LOYALTY DIMEDIASI OLEH CUSTOMER SATISFACTION (STUDI KASUS DI TOKO ONLIE PERSEWAAN ALAT-ALAT GRILL) - Nazila Wiji Rochmah; Laily Muzdalifah (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2024)
This research aims to examine the influence of product quality and price perception on customer loyalty which is mediated by customer satisfaction in an online grill equipment rental shop. A sample of 70 respondents had their data processed using the Smart PLS 4 program. The research results show that: product quality has a direct and significantly positive effect on customer loyalty. Price perception also has a direct and significantly positive effect on customer loyalty, price perception has a direct and significantly positive effect on customer satisfaction. Meanwhile, product quality has no significant effect on customer satisfaction, customer satisfaction has a direct and significant positive effect on customer loyalty, customer satisfaction can positively mediate the relationship between product quality and customer loyalty. Customer satisfaction does not mediate significantly between product quality and customer loyalty. This research enriches information/theory regarding the relationship between products, price perceptions, customer satisfaction and customer loyalty and offers a new approach to the relationship between variables.